Halal Food Purchasing Behavior of The Millennial Generation in Indonesia - Liza Nora; Nurul Sriminarti (Journal of Consumer Sciences, 2025)
Background: The Muslim millennial population plays an increasingly important role in the future development of the halal market. Therefore, understanding the consumer behavior of Indonesian Muslim millennials and the factors that influence their decisions when choosing halal products and services is essential. Purpose: This study aims to explore Indonesian millennial consumers' behavior toward halal food products by integrating the Theory of Planned Behavior (TPB) with additional variables of halal awareness and religious belief. Method: This study employs quantitative methods. Data were collected through purposive sampling using online questionnaires distributed via Google Forms to 267 millennial respondents born between 1981 and 1996 in Indonesia. Data were analyzed using descriptive methods and Structural Equation Modeling (SEM). Findings: Halal awareness does not affect purchase intention. In contrast, attitudes, subjective norms, perceived behavioral control, and religious beliefs significantly influence purchase intention. Additionally, purchase intention significantly influences purchase behavior, acting as a mediator between perceived behavioral control and religious beliefs. Conclusions: These findings provide new insights into the factors influencing consumer purchasing behavior, particularly among millennials, and highlight the importance of psychological and social factors in halal product choice. The study is expected to contribute significantly to the development of marketing strategies in markets sensitive to religious issues. Research implication: To increase millennials' purchase intention toward halal food, managerial strategies should focus on quality, safety, product conformity with health and sustainability values, and the use of social influence through social media, influencers, and community campaigns. Additionally, strategies should facilitate access and purchasing, offer competitive prices, and ensure convenience in the purchasing process so that millennials feel in control of their decisions.